2019
DOI: 10.3390/nu11020249
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and Its Impact on Skin Anatomy, Physiology, and Physiopathology: A Comprehensive Review of the Literature

Abstract: Skin serves as the first protective line and barrier of the body. Like many other organs, skin can be affected by several disorders in response to external factors such as pathogens, ultraviolet light, and pollution, as well as endogenous alterations related to aging and/or oxidative stress disturbance. Researchers have reported new insights into how skin cells are altered in response to caloric restriction diets in mammals. One of the most well-known caloric restriction diets is the Ramadan intermittent fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 77 publications
0
39
0
2
Order By: Relevance
“…Moreover, fasting treats diabetes (Ku, Ramos & Fung, 2017), treats skin diseases (Bragazzi et al, 2019), reduce obesity, hypertension, asthma, and arthritis, potentially prevent and treat diseases (Longo & Mattson, 2014), reduce inflammation, improve circadian rhythm, improve autophagy, resilience against stress, and modulation of intestinal mirobiota (Paoli, Tinsley, Bianco & Moro, 2019), improve metabolism, slow aging, and slow the spread of disease (Anton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fasting treats diabetes (Ku, Ramos & Fung, 2017), treats skin diseases (Bragazzi et al, 2019), reduce obesity, hypertension, asthma, and arthritis, potentially prevent and treat diseases (Longo & Mattson, 2014), reduce inflammation, improve circadian rhythm, improve autophagy, resilience against stress, and modulation of intestinal mirobiota (Paoli, Tinsley, Bianco & Moro, 2019), improve metabolism, slow aging, and slow the spread of disease (Anton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…National Health and Nutrition Examination Surveys (NHANES) 2007-2010 indicate that among US population 75% consumed less fruit and 87% consumed fewer vegetables than recommended [30]. The accumulation of glycoxidation products such as carboxymethyl lysine (CML) and pentosidine in cutaneous collagen promotes skin aging.Bragazzi et.al, 2019 reported that chronic caloric restriction decreased the glycation rate of skin proteins, resulting in the reduction of age-related accumulation of these metabolites in cutaneous collagen [31]. Mekić et.al, 2019 reported that better adherence to the Dutch Healthy Diet Index (DHDI) was significantly associated with less wrinkles among women but not in men.…”
Section: Diet and Nutritionmentioning
confidence: 99%
“…In another study, fasting was found to modulate the IGF-1 receptor (IGF-1R)/epithelial growth factor (EGF) receptor (EGFR) and the Akt/mTOR pathways, which are dysregulated in obesity and may lead to skin cancer [44] . However, Bragazzi et al, 2019 concluded that physicians should be instructed in recognizing rare dermatological disorders associated with fasting, such as Prurigo pigmentosa (PP) [45] . Damiani et al, 2019 reported significant decrease in the "Psoriasis Area and Severity Index" (PASI) score after the Ramadan fasting [38] .…”
Section: Letter To the Editormentioning
confidence: 99%